A Unique Sulfotransferase-Involving Strigolactone Biosynthetic Route in Sorghum - Wu, Sheng; Li, Yanran (Frontiers in Plant Science, 2021)
LOW GERMINATION STIMULANT 1 (LGS1) plays an important role in strigolactones (SLs) biosynthesis and Striga resistance in sorghum but the catalytic function remains unclear. Using the recently developed SL-producing microbial consortia, we examined the activities of sorghum MAX1 analogs and LGS1. Surprisingly, SbMAX1a synthesized 18-hydroxy-carlactonoic acid (18-hydroxy-CLA) directly from carlactone (CL) through four-step oxidations. The further oxidated product orobanchol (OB) was also detected in the microbial consortium. Further addition of LGS1 led to the synthesis of both 5-deoxystrigol (5DS) and 4-deoxyorobanchol (4DO). Further biochemical characterization found that LGS1 functions after SbMAX1a by converting 18-hydroxy-CLA to 5DS and 4DO possibly through a sulfonation-mediated pathway. The unique functions of SbMAX1 and LGS1 imply a previously unknown synthetic route towards strigolactones.